An Evaluation of Pile-Raft Interaction in Cohesive Soils using 3D Finite Element Method - Endra Susila; Muhammad Yoke Syahputra; Andhika Sahadewa; Karina Meilawati Eka Putri (Journal of Engineering and Technological Sciences, 2019)
This paper presents the results of a numerical study of soil-structure interaction in a piled-raft foundation system in clay soil by reviewing the deformation and load transfer mechanism of the piled-raft foundation system. ABAQUS was used to evaluate the interaction in the system, while a Mohr-Coulomb constitutive model was chosen to model the clay soil. Verification of the model was conducted by comparing the simulation result to an experimental laboratory result. The verification result showed that the model used in this research agreed well with the experimental laboratory research. Subsequently, a parametric study was performed by varying the pile spacing, raft size, pile length, and raft thickness. A parametric study was conducted on very stiff and hard clays. This study concludes that the load transfer mechanism in a piled-raft foundation system between the pile and raft foundation occurs after the pile reaches its ultimate capacity and is in the plastic zone.